First record of melanism in the northern palm squirrel Funambulus pennantii in Delhi, India - Puri, Kanchan; Joshi, Ritesh (Therya Notes, 2023)
Melanism is a rare phenomenon in animals and is caused by an excessive development of dark pigments (melanin) that produces a darkening of the skin and hair of animals. In this note, we report and illustrate an observation of melanism in a northern palm squirrel, Funambulus pennantii, in an urban park, Siri Fort Park, in the National Capital Territory of Delhi, northern India. A northern palm squirrel with melanism was observed during field studies. The individual was partially black, with a blackish head, neck, ears, and forelimbs, while the rear part of the body and tail were of normal color. Because no cases of melanism in the northern palm squirrel have been reported in the region, this report constitutes the first record of the presence of the northern palm squirrel with melanism in the Territory of the Delhi Union. The above will open new dimensions in the natural history of the species. More studies are needed to help understand this rare phenomenon in the species, and the ecological and physiological implications, such as survival, of the species' populations.